The Effect of Subthalamic Nucleus - Deep Brain Stimulation and Different Stimulation Frequencies on Cerebral Hemodynamics in Parkinson's Disease: A Transcranial Doppler Study - Koban, O.; Yildizgören, M.T.; Aras, M.; Oral, S.; Uyanık, S.A.; Serarslan, Y.; Okuyucu, E.E. (Elsevier B.V., 2020)
Objectives: To investigate the effect of deep brain stimulation of the subthalamic nucleus (STN-DBS) and to compare low-frequency versus high-frequency STN-DBS on hemodynamic parameters of the middle cerebral artery between patients with advanced Parkinson's disease and age-sex matched healthy controls. Patients and Methods: Eighteen patients with advanced Parkinson's disease (PD) with bilateral STN-DBS and 18 control subjects underwent Transcranial Doppler Ultrasound (TCDU) were included in the study. The hemodynamic parameters including blood flow velocity (FV), pulsatility index (PI) and, resistance index (RI) of the right middle cerebral artery (MCA) were measured and compared during the phases using TCDU. The first DBS-off, the second low-frequency DBS of 60 Hz, and the third high-frequency DBS of 130 Hz were compared. Results: PD patients had significantly higher MCA-PI values compared with controls (0.99 ± 0.27 vs. 0.82 ± 0.14) (p = 0.031). Also, the MCA-PI values were higher in the low-frequency DBS (0.94 ± 0.14) and high-frequency DBS (0.93 ± 0.16) than in the controls (0.82 ± 0.14) (p = 0.022 and p = 0.041, respectively). There were no significant differences of FV and RI values among the DBS-on, DBS-off and, controls. The RI values were higher in the PD patients than in the controls, although these were not statistically significant. Also, PI values of the MCA decrease in different frequencies (60 Hz or 130 Hz). Conclusion: The results of this study showed that MCA-PI values are higher in advanced PD compared with controls. These indices indicate that MCA resistances and impedances are increased in advanced PD. Low- or high-frequency DBS treatment have beneficial effect to reduce high PI in advanced PD patients. © 2020 Elsevier B.V.
Keywords: Blood Flow Velocity; Deep Brain Stimulation; Pulsatility Index; Resistance Index; Transcranial Doppler Ultrasound